Pendidikan Agama Islam dalam UU Nomor 20 Tahun 2003 Tentang Kebijakan Sistem Pendidikan Nasional - Mutia Miftachul Janna; Sangkot Sirait; Mahmud Arif (Universitas Islam Lamongan, 2025)
This article examines Islamic Religious Education within the framework of Law No. 20 of 2003 regarding the National Education System. It highlights the government's efforts to incorporate Islamic Religious Education (IRE) into the national education system as a means to instill Islamic values in students, thereby fostering their religious and ethical character. The law recognizes Islamic Education as part of formal, non-formal, and informal educational institutions, regulates it as a subject in the curriculum across all educational levels, integrates Islamic values into the educational system, and asserts that religious education serves as a source of values and is integral to national education. The author employs the Literature Study method or Systematic Literature Review (SLR), which enables the author to identify, review, and analyze existing findings, resulting in a hierarchically structured and informative text. Furthermore, while this article focuses on the legal perspective provided by Law No. 20 of 2003, it contrasts with other research that primarily analyzes the implementation of IRE in practice rather than its legal framework. Many studies investigate how effectively these policies are realized in educational settings, often highlighting challenges faced in execution. This approach underscores the importance of not only establishing legal recognition for Islamic education but also ensuring that these policies are effectively implemented to achieve their intended outcomes in fostering a well-rounded educational experience for students.